Ghost Lands: Spirit, Space, and the Construction of Cosmology in Native Ghost Stories - (:unkn) unknown (My University, 2022)
There are many narratives of Native ghosts in the settler American literary imagination that dehumanize Native people, presenting Native nations as absent from the current time and space. While scholars have addressed the Native-erasure function of these narratives, relatively few have thus far explored how Native writers might compose ghost stories that fundamentally construct a cosmology outside of colonial frameworks and histories. I am proposing, then, to consider what Native stories of haunting can mean outside of this context by examining their constructed cosmologies on their own terms. I aim to broaden the category of what we may consider a “ghost story” specifically by examining Native writers’ constructions of spirit, space, and cosmology. A great deal of scholarship focuses merely on symbolic or folkloric readings of spirits, denying the material, real-world ramifications of ghosts in literature. Yet my reframing of ghost stories can prioritize Native presence on this continent and emphasize haunting as a crucial narrative form of constructing and understanding a version of the universe.In this dissertation, I explore how Native writers’ representations of spirits construct cosmological systems, at term I define here as: conceptions of how energy and matter may interact across space-time. I will demonstrate how Native authors LeAnne Howe, Stephen Graham Jones, and Brandon Hobson construct culturally informed cosmologies with their literary presentations of spirits, thus transforming dominant thought systems and perceptions of reality. This work can have transformational political potential. The reconfigurations of space, energy, matter, and power that are made apparent in a haunting have lasting implications for the sovereignty of Native nations, ecology, and other pressing sociopolitical subjects discussed in this dissertation. Further, the imagination of space — including the imagination of the spirits and other beings occupying that may occupy a space — is a project central to both colonialism and decolonization. The “ghost story” often represents liminality among worlds and forms of embodiment, and I read the genre even more deeply as a non-binary means of approaching spirit, space, and cosmology. Thus, this dissertation focuses on Native writers’ active dismantling of life/afterlife, human/nonhuman binaries in ghost fiction. What I hope will result from this dissertation study is a more complex reading of Native literary ghost stories, as well as an expanded conception of how the “ghost story” may function to construct spirit, space, and cosmology and have a lasting impact on the lived experience of all beings.